2022
DOI: 10.3390/antiox11020232
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene: A Natural Arsenal in the War against Oxidative Stress and Cardiovascular Diseases

Abstract: Lycopene is a bioactive red pigment found in plants, especially in red fruits and vegetables, including tomato, pink guava, papaya, pink grapefruit, and watermelon. Several research reports have advocated its positive impact on human health and physiology. For humans, lycopene is an essential substance obtained from dietary sources to fulfil the body requirements. The production of reactive oxygen species (ROS) causing oxidative stress and downstream complications include one of the major health concerns world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 228 publications
1
39
0
Order By: Relevance
“…Lycopene may prevent inflammation, pain and cardiovascular disease. It may also regulate blood cholesterol levels and protect against high blood pressure and coronary heart disease [ 11 ]. As the most common carotenoid found in the blood, its consumption is very important.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lycopene may prevent inflammation, pain and cardiovascular disease. It may also regulate blood cholesterol levels and protect against high blood pressure and coronary heart disease [ 11 ]. As the most common carotenoid found in the blood, its consumption is very important.…”
Section: Resultsmentioning
confidence: 99%
“…As the most common carotenoid found in the blood, its consumption is very important. Due to its antimicrobial, antioxidant and anti-inflammatory role, lycopene is thought to be effective in preventing the effects of malnutrition [ 11 ]. In this study, the levels (101.23 to 101.46 ± 0.46 mg/100 g) obtained in the peels confirmed that tomato by-products are significant sources of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of lycopene towards reactive forms of ROS can be predicted through three mechanisms such as (Figure 2): Besides quenching singlet molecular oxygen, lycopene is also known to act on other free radicals like hydrogen peroxide, nitrogen dioxide, and hydroxyl radicals [42]. Lycopene is believed to increase the cellular antioxidant defense system by regenerating non-enzymatic antioxidants, such as vitamins E and C, from their radicals [43].…”
Section: Antioxidant Effects Of Lycopenementioning
confidence: 99%
“…Lycopene, one of the main carotenoids present in tomatoes has several beneficial properties and acts as a potent antioxidant, protecting cells against oxidative damage and thereby reducing the risk of chronic diseases [ 5 ]. Other studies mention that this compound is an ingredient with many positive contributions to human health and physiology [ 6 ]. It is a hydrophobic antioxidant that confers the red color pigment characteristic of tomatoes and increases with ripening [ 7 ].…”
Section: Introductionmentioning
confidence: 99%